KINERJA KARYAWAN PT. DATA ENERGI INFOMEDIA KABUPATEN SRAGEN - Savitri, Savitri; Wardani, Kalis Kusuma (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
The research’s purpose was to describe the influences of workload, work stress, and occupational safety and health on employee’s performance on PT Data Energi Infomedia’s employees. This is a quantitative reseasrch with explanatory approach. The population are employees of PT. Data Energy Infomedia Sragen, 77 (seventy-seven) people as samples. Documentation and questionnaires used to collect the data, then analyzed with SPSS. The result’s research shows that workload, work stress, and occupational safety and health have a significant and simultaneous influence on employee’s performance. It shown by the rate of F-significance < α (0.000 < 0.05) with 0,444 adjusted R-square, which means that they have 44,4% contribution of Occupational Safety and Health on employee’s performance, and 55,6% by other variables beyond. The workload significantly affect the employee’s performance of 0.000. The work stress also significantly affect the employee’s performance on 0.017, while occupational safety and health have significantly affect on employee’s performance of 0.000.